‘Apprendre à voir’: the quest for insight in George Sand’s novels - Mathias, M (2011)
This thesis examines the novels of George Sand (1804-1876) and analyses representative examples from her entire œuvre. Its overall aim is to re-evaluate Sand’s standing as a writer of intellectual interest and importance by demonstrating that she is engaging with a cultural and intellectual phenomenon of particular relevance to the nineteenth century: the link between different ways of seeing and knowledge or understanding, which I term ‘insight’. The visual dimension of Sand’s novels has so far been overlooked or reduced to a rose-tinted view of the world, and my study is the first to examine vision in her work. I argue that Sand demonstrates a continuous commitment to ways of engaging with the world in visual terms, incorporating conceptual seeing, prophetic vision, as well as physical eyesight. Contesting the prevailing critical view of Sand’s œuvre as one which declines into blandness and irrelevance after the 1850s, this thesis uncovers a model of expansion in her writing, as she moves from her focus on the personal in her early novels, privileging internal vision, to wider social concerns in her middle period in which she aims to reconfigure reality, to her final period in which she advocates the physical observation of the natural world. Rejecting the perception of Sand as a writer of sentiment at the expense of thought, this study argues that her writing constitutes a continuous quest for understanding, both of the physical world and the more abstract, eternal ‘vérité’. I show that Sand transcends binary divisions between science and art, the detail and the whole, the material and the abstract, and that she ultimately promotes a multidisciplinary approach to understanding the world. This also enables me to reassess Sand’s poetics by arguing that her rejection of the mimetic model is founded on her conception of the world as multiple and constantly evolving.